KESENJANGAN EKSPEKTASI AUDITOR INTERNAL DENGAN AUDITEE - Ika Rossi Agustin; Rachma Agustina (Behavioral Accounting Journal, 2021)
Based on the result of Financial Report of Jombang District Government or Laporan Keuangan Pemerintah Daerah (LKPD) Fiscal Audit, 2019, The Audit Board of The Republic of Indonesia (Badan Pemeriksa Keuangan Republik Indonesia, BPK) gives a proper unqualified opinion or wajar tanpa pengecualian (WTP).While the results of Financial and Development Supervisory Agency mapping against the Inspectorate of Jombang Regency, it is at level 3 capability (developing). However, there are still some problems, demands, and complaints about the performance of government auditors which indicating public dissatisfaction of local government internal auditor’s performance. On the other hand, the assessment result of local government shows relatively good score. This study aims to investigate the expectation gaps phenomena between auditors and auditees on independence and audit quality. This research was used the quantitative research and data collection method which is a questionnaire then analyzes data using descriptive analysis and an independent t-test. The results of this study indicate that there were an expectation gaps between internal government supervisory apparatus and auditees related to the independence of internal auditors, and also an expectation gap between internal government supervisory apparatus and auditees regarding to the audit quality.